Management of a Nulliparous IVF Patient with a Declined Ovarian Reserve After Discovery of an Atypical Ovarian Endometriotic Cyst - Ke X; Liang XF; Wang F (Dove Medical Press, 2023)
Xue Ke, Xue-Fei Liang, Fang Wang Department of Reproductive Medicine, Chengdu Women's and Children's Central Hospital, School of Medicine, University of Electronic Science and Technology of China, Chengdu, People's Republic of ChinaCorrespondence: Fang Wang, Chief Department of Reproductive Medicine, Chengdu Women's and Children's Central Hospital, School of Medicine, University of Electronic Science and Technology of China, Chengdu, People's Republic of China, Email wangfcd2022@163.comPurpose: Endometriosis (EM) is a common cause of infertility, and an ovarian endometriotic cyst may affect the ovarian reserve, ovulation, and endometrial receptivity. The majority of EM cases are benign; however, EM may also be prone to malignant transformation, associated with infiltrative growth, and recurrent or distant metastasis. In this study, we report the management of an atypical cyst discovered through ovarian endometriotic cyst puncture prior to controlled ovarian stimulation (COS).Case Presentation: The patient required in vitro fertilization treatment due to EM and bilateral fallopian tube obstruction. Prior to initiating gonadotropin (Gn) treatment, the right ovarian EM cyst was punctured; cytological pathology of the obtained fluid revealed an atypical morphology. Subsequently, the case was discussed with the patient and ethically reviewed. Gn was initiated according to the patient's wishes, and six day-3 embryos were finally obtained and cryopreserved. Afterwards, laparoscopic cystectomy of the ovarian endometrioma revealed no malignant transformation. The patient achieved clinical pregnancy after resuscitation and transplantation of the embryo.Conclusion: In summary, patients with EM-associated infertility are at risk of ovarian cancer formation when undergoing assisted reproduction treatment; therefore, this risk should be evaluated and minimized before initiating such treatment.Keywords: ovarian cyst, endometriosis, atypical cyst, in vitro fertilization, cyst puncture